Pengaruh Customer Engagement, Brand Trust, Promosi Terhadap Loyalitas Pelanggan di Brand Executive - Tegar Wijaya Suwardi; Dony Oktariswan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Increasingly tight business competition requires companies to focus more on maintaining customer loyalty as one of the most important assets in long-term business sustainability. One of the problems that often occurs is the low level of customer loyalty even though promotional strategies have been carried out actively and continuously. This study aims to determine and analyze the effect of Customer Engagement, Brand Trust, and Promotion on customer loyalty at Brand Executive. This study uses a quantitative approach with a survey method by distributing questionnaires to 80 respondents who are Brand Executive customers. Data analysis techniques used in this study include classical assumption tests, multiple linear regression analysis, and partial tests (t-tests). The results of the study indicate that the three independent variables, namely Customer Engagement, Brand Trust, and Promotion, have a significant effect on customer loyalty. These findings indicate that customer involvement and trust in the brand are the main factors in building long-term loyalty. However, promotions that are carried out appropriately and relevantly also make a positive contribution to strengthening customer loyalty to Brand Executive.